Research of the spin-Hamiltonian parameters and tetragonal distortion for Dy3+ octahedral clusters in the tetragonal phase of Rb2NaYF6. (28th May 2017) - Mei, Yang; Liu, Hong-Gang; Zheng, Wen-Chen
Graphical abstract: The EPR parameters for Dy 3+ in Rb2 NaYF6 were explained theoretically and the obtained phase transition was in good agreement with the experimental results. Relatively larger disparity between calculated and observed Ai 163 was also discussed. Abstract: The spin-Hamiltonian parameters ( g factors gi and hyperfine structure constants Ai 161, Ai 163, where i = || or ⊥) for 161 Dy 3+ and 163 Dy 3+ isotopes in the Y 3+ site of tetragonal Rb2 NaYF6 crystals are calculated by the diagonalization of energy matrix plus perturbation formulas. The calculated results are reasonably coincident with the experimental values. The calculations suggest that the constants Ai 161 and Ai 163 are negative and positive, respectively and the (DyF6 ) 3− octahedral clusters are, similar to (YbF6 ) 3− and (CeF6 ) 3− clusters in Rb2 NaYF6, tetragonally-elongated. The results (containing the reasonableness of tetragonal distortion of (DyF6 ) 3− cluster and the causes of the relatively larger disparities between the calculated and observed Ai 163 ) are discussed.